The regulation of emotion - Philippot, Pierre, 1960-; Feldman, Robert S. (Robert Stephen), 1947- (Lawrence Erlbaum, 2004)
The aim of this volume is to present, in an integrated framework, the most contemporary perspectives on emotion regulation. The book includes empirically-grounded work and theories that are central to our understanding of the processes that constitute emotion regulation and their consequences.